Afghanistan 2014 : the decision point - Sultan, Dr Maria ([S.l.] : South Asian Strategic Stability Institute, 2013)
...
Keywords: Afghan War (2001-); Afghanistan; Military policy; Relations; Strategic aspects of individual places; United States